An Examination of Lumbar and Ventricular Cerebrospinal Fluid Findings in Children with Tuberculous Meningitis and Hydrocephalus - Mwenda, Lona Albertha (Department of Paediatrics and Child Health, 2020)
Background: Childhood tuberculous meningitis (TBM) has poor outcomes. These are often associated with delayed diagnosis because early diagnosis and treatment is challenging. Existing diagnostic criteria use CSF characteristics to suspect TBM. However, lumbar and ventricular CSF may differ. These differences have not been well characterised Sometimes only ventricular CSF is available and decisions about surgical treatment may be influenced by CSF characteristics. This study examined CSF parameters from lumbar and ventricular compartments in patients with TBM and hydrocephalus who required neurosurgical procedures, their CSF temporal profiles, differentials between compartments, and factors that may influence these results. Methodology: A descriptive cross-sectional study was conducted including data from two prospective TBM studies. Children treated for TBM and hydrocephalus at Red Cross War Memorial Children’s Hospital with lumbar and/ or ventricular samples were selected. Pooled lumbar verses ventricular samples and paired time-linked samples in individual patients were analysed. Differences in CSF cell counts and biochemistry parameters across compartments were analyzed using Wilcoxon signed rank test, and temporal profiles graphically presented. Associations between laboratory, clinical and radiological data were analyzed using Mann-Whitney’s U test. To test for associated factors, results of the nature of hydrocephalus (level of CSF obstruction) and spinal imaging were analyzed where available. Association between CSF parameters and morbidity was analyzed. Results: Eighty-one patients were studied, 29 had time-linked paired CSF. The mean patient age was 36 months (2- 156 months), 93% were HIV-uninfected, and the mortality rate was 13.6%. Seventy-two percent had communicating hydrocephalus, 16% non-communicating, and 12% uncertain (unable to demonstrate level of block). Medians of admission lumbar CSF showed low glucose (2.2 mmol/L), low chloride (112 mmol/L), raised protein (2g/L) and elevated white cell count (165 x 106 /L). Corresponding values for admission ventricular CSF were minimally affected glucose (3mmol/L), mildly low to normal chloride (114.5mmol/L), normal to mildly raised protein (0.5g/L) and less elevated white cell count (22 x 106 /L). In paired samples, all parameters were significantly different between lumbar and ventricular CSF. Ventricular CSF showed milder aberrations than lumbar CSF: lower protein and total white cell count, higher glucose and chloride. All paired samples showed higher lumbar CSF protein; lower lumbar CSF chloride in almost 80%; lower lumbar CSF glucose in 96%. Analysis of possible factors was limited by the small patient numbers who had full brain and spine imaging, and also paired CSF samples (n=17). However, maximum lumbar CSF protein was associated with severity of spinal disease on imaging. The lymphocyte ratio between lumbar and ventricular CSF was higher in patients with non-communicating and uncertain hydrocephalus. CSF parameters normalized slowly. White cell count and lymphocyte CSF differential were associated with favorable outcome in survivors. Conclusion: Lumbar CSF depicted a typical TBM pattern. Ventricular CSF differed: CSF parameters were less abnormal in both pooled analysis and across individual paired samples. Spinal disease severity and nature of hydrocephalus may affect this differential. The CSF compartment sampled is therefore clinically relevant when interpreting CSF characteristics for diagnostic and treatment decisions. Studies of TBM diagnosis, pathophysiology, biomarkers and drug concentrations should consider these differences.